MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERPADU DI SMA-IT DARUL HIKAM BANDUNG - Suprapto Suprapto (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
Integrated learning is a learning approach which involves multiple course subjects in order to provide meaningful experience to the students. Integrated education can be realized through the formulation of the vision and mission from the school that need to be achieved, school’s objectives and programs (the strategic plan of the school), the formation of institution culture that reflects the blend of values and learning, which is operationally in the form of curriculum and extra-curriculum plan that formulated such a way so that the fundamental values of Islamic teaching and the science (general education) are integrated coherently. The implementation of integrated PAI learning in Darul Hikam Senior High School is clearly seen on the typical curriculum (kurhas) of character education with developing 7 values (sincere, patient, trustworthy, discipline, caring, smart and good deeds) through Taqwa Character Building (TCB) as mentioned above. This TCB is in line with the philosophy and vision built by Darul Hikam Senior High School. Moreover, TCB is also aligned with the objectives of the national education.